Мікрохвильова патологія мозку, що виникає за дії НВЧ-поля - Білокриницький, В.С. (№5, 2007)
The articles describes theoretical fundamentals of microwave frequency electromagnetic damaging action on human central nervous system developed by the author based on long-term experimental studies. The attention is focused on the new trend in science and search of individual protection from damaging influence of electromagnetic smog.